2010
DOI: 10.1021/jz100214h
|View full text |Cite
|
Sign up to set email alerts
|

Proton Transfer in Adenine−Thymine Radical Cation Embedded in B-Form DNA

Abstract: On the basis of pK a measurements, it has been predicted that proton transfer will not occur in the radical cation of the A/T base pair (A: adenine, T: thymine). Testing this prediction, we have performed simulations as a function of time on an A/T oligomer missing one electron, in solution, using the code CP2K. We find that proton transfer occurs rapidly at temperatures below room temperature. We suggest that the difference in behavior of (A/T)·+ from that predicted on the basis of pK a measurements is the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 22 publications
3
30
1
Order By: Relevance
“…It was found that immediately upon introduction of the hole its wavefunction is spread over 5 adenines, the length of the QM region in this simulation [8,9]. Within 20 fs, however, the hole is localized on a single one of these adenines [8,10]. It was shown that the contraction of the hole, that we have called self-trapping, is due to the polarization set up by the hole in the surrounding water [10,11].…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…It was found that immediately upon introduction of the hole its wavefunction is spread over 5 adenines, the length of the QM region in this simulation [8,9]. Within 20 fs, however, the hole is localized on a single one of these adenines [8,10]. It was shown that the contraction of the hole, that we have called self-trapping, is due to the polarization set up by the hole in the surrounding water [10,11].…”
mentioning
confidence: 73%
“…Perhaps the shortest time for reorganization is that involved in the response of the water to introduction of a hole. This time has been deduced by simulations using cp2k for a DNA consisting of a series of ATs in water [8,9]. It was found that immediately upon introduction of the hole its wavefunction is spread over 5 adenines, the length of the QM region in this simulation [8,9].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…23,24 Conwell et al demonstrated that the water hydration induces hole localization on one base, instead of several bases. 16 In our calculations, if the waters are dealt with quantum mechanics, which the distance with the helix less than 8 angstroms, the hole would localize on waters.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15] Related studies pointed out that DNA is sensitive to environmental factors, such as solute, temperature et al Recently Conwell group pointed out that proton transfer appears on radical cation of AT base pair at low temperature in water. 16 At higher temperature, what would happen? In this paper, we investigate whether proton transfer could be found at higher temperature in water, then the proton behaviors under the external electric field are discussed.…”
Section: Introductionmentioning
confidence: 99%